GENDER AND PEACE-BUILDING: NAWURI WOMEN AND PEACE-BUILDING INITIATIVES IN THE KPANDAI DISTRICT IN THE NORTHERN REGION OF GHANA - Mbowura, C. (UDS International Journal of Development, 2022)
Scholarship on Nawuri history, sociocultural, economic and political institutions and organizations has provided little space for gender issues. Similarly, the narratives on the Nawuri-Gonja conflict, particularly its resolution and search for peace, have failed to situate peace-building encounters and initiatives within gender perspectives. This study examines the roles of Nawuri women in peace-building in Kpandai and its environs after the Nawuri-Gonja conflict of the 1990s. It examines the sociocultural tools and nomenclatures – the magico-religious rituals, songs, demonstrations and outreach programmes – that Nawuri women utilized to promote peace and advance peace-building initiatives in Kpandai and its environs after the Nawuri-Gonja conflict. By blending together data from monographs, field research and archival materials, this study constructs a coherent narrative on the contributions of Nawuri women to peace-building in Kpandai and its environments over the past three decades. It argues that Nawuri women appropriated issues and events in their sociocultural settings to advance the course of peace and peace-building in their environment after the Nawuri-Gonja conflict of the 1990s. Keywords: Conflict, Peace-building, alijii, ejii, chankpana, Nawuri, Gonja, sociocultural, Baya, women.